2012
DOI: 10.4049/jimmunol.1102053
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Immune Evasion Mediated by Host Cell-Derived Microvesicles

Abstract: The innate immune system is the first mechanism of vertebrate defense against pathogen infection. In this study, we present evidence for a novel immune evasion mechanism of Trypanosoma cruzi, mediated by host cell plasma membrane-derived vesicles. We found that T. cruzi metacyclic trypomastigotes induced microvesicle release from blood cells early in infection. Upon their release, microvesicles formed a complex on the T. cruzi surface with the complement C3 convertase, leading to its stabilization and inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(200 citation statements)
references
References 58 publications
4
191
1
1
Order By: Relevance
“…The latter possibility is supported by recent experiments showing that host cells infected with Leishmania spp. or T. cruzi released EVs contained both host and parasite proteins (38,40,41). Indeed, immunoelectron microscopy studies confirmed that EVs released by T. cruzi do not have a homogeneous composition, since some vesicles were found to contain the membraneanchored MASPs while other vesicle populations contained clathrin (58).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The latter possibility is supported by recent experiments showing that host cells infected with Leishmania spp. or T. cruzi released EVs contained both host and parasite proteins (38,40,41). Indeed, immunoelectron microscopy studies confirmed that EVs released by T. cruzi do not have a homogeneous composition, since some vesicles were found to contain the membraneanchored MASPs while other vesicle populations contained clathrin (58).…”
Section: Discussionmentioning
confidence: 61%
“…A similar modulation of macrophage responses was observed following exposure to purified Leishmania exosomes, a strategy that enhances intracellular parasite survival (38,39). Mechanistic studies suggest that in the early stages of infection by T. cruzi, parasites promote the release of plasma membrane vesicles from the host cell, which may contribute to parasite survival in the circulatory system, an event thought to help mediate host cell invasion (40).…”
mentioning
confidence: 60%
“…In Trypanosoma cruzi, Cestari et al (2012), demonstrated that metacyclic trypomastigotes forms when in contact with the monocytic THP-1 cell line, release MVs that inhibit C3 convertase, and aid the parasite to invade host cells. Recently, other groups have shown that MVs from T. cruzi have different sizes, and different effects.…”
Section: Trofozoites From Giardia Intestinalis Respond To Environmentmentioning
confidence: 99%
“…There are numerous examples in the literature of protozoa releasing large amounts of material into the extracellular space as a form of cellular communication with host cells (Garcia-Silva et al, 2014;Linhares-Lacerda et al, 2015;Fernandez-Calero et al, 2015;Cestari et al, 2012). In Giardia intestinalis, the diarrhoea and malabsorption could be a direct result of the interaction of the parasite with the intestinal epithelium which might be mediated by the parasite itself, or by substances it secretes or by MVs that could alter neighbouring cells.…”
Section: Exosome and Microvesicles Content Can Alter Neighbouring Cellsmentioning
confidence: 99%
“…Cestari, et al [54] reported that T. cruzi also induces release of exosomes from the host cells and that these vesicles bind to the parasites and protect them to complement-mediated lysis. Recently, Ramirez and thors also reported that these results varied according to the strain of T. cruzi used.…”
Section: Exosomes In the Protozoan Trypanosoma Cruzimentioning
confidence: 99%